Avaliação comparativa in vivo da eficácia do óleo de melaleuca, clorexidina e listerine sobre streptococcus mutans e microrganismos totais na saliva - Nogueira, Marianne Nicole Marques [UNESP]; Correia, Marilia Ferreira [UNESP]; Fontana, Amanda [UNESP]; Bedran, Telma Blanca Lombard [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP] (My University, 2013)
Objective: To compare the efficacy of the mouthwashes 0.12% chlorhexidine, Listerine, and 0.5% and 2% Melaleuca Alternifolia oil against the salivary levels of Streptococcus mutans and total microorganisms. Methods: This study was double-blind controlled and paired clinical assay. Twenty-six volunteers aged 21 to 35 years old were enrolled. At baseline, 1 mL of unstimulated saliva was collected from each subject, 1 and 15 min after mouthrinsing with the following solutions: sterile distilled water, 0.12% chlorhexidine digluconate, Listerine (©Johnson & Johnson do Brasil), 0.5% and 2% concentrations of Melaleuca Alternifolia (Sigma-Aldrich). The volunteers used all the evaluated mouthrinses with a 15-day interval between the solutions. Immediately after rinsing, saliva was collected and serial dilutions were performed, followed by plating in blood agar culture medium for growth of total microorganisms and SB-20 (Sucrose-Bacitracin agar) for growth of S. mutans, and incubation at 37 °C for 48 h in microaerophilia. After incubation, the number of colonies was counted and expressed as colony forming units (UFC/mL). Results: Chlorhexidine showed antimicrobial action by reducing total microorganisms and S. mutans, while the action of 0.5% Melaleuca Alternifolia was similar to that of distilled water. Listerine and 2% Melaleuca Alternifolia oil reduced total microbial counts by 11% and 9% respectively, and S. mutans by 20% and 11%. Conclusion: A single rinse with 0.12% chlorhexidine is effective in reducing the levels of total microorganisms and S. mutans present in saliva. Under the same testing conditions, Listerine and 0.5% and 2% Melaleuca Alternifolia oil presented lower efficacy than chlorhexidine.

Objetivo: Comparar a eficácia dos enxaguatórios bucais: clorexidina 0,12%, Listerine e óleo de Melaleuca Alternifolia 0,5% e 2% sobre os níveis salivares de Streptococcus mutans e microrganismos totais. Métodos: O estudo foi um ensaio clínico, controlado, duplo cego e emparelhado. Para tanto foram selecionados 26 voluntários com idade entre 21 - 35 anos. Foi coletada de cada participante, no baseline, a quantidade de 1 mL de saliva não estimulada, 1 e 15 min após os bochechos com as seguintes soluções: água destilada estéril, digluconato de clorexidina 0,12%, Listerine (©Johnson & Johnson do Brasil), Melaleuca Alternifolia (Sigma-Aldrich St Louis, MO, USA) nas concentrações de 0,5% e 2%. Os participantes fizeram uso de todos os enxaguatórios bucais pesquisados, com intervalo de 15 dias entre cada solução. Imediatamente após o bochecho, foi coletada a saliva e realizadas as diluições seriadas, seguidas de plaqueamento em meio de cultura Agar sangue para o crescimento de microrganismos totais e SB- 20 (Agar Sacarose Bacitracina) para S. mutans, mantidos por 48h a 37°C em microaerofilia. Após o período de incubação, as colônias foram contadas e transformadas em unidades formadoras de colônias (UFC/mL). Resultados: A clorexidina mostrou ação antimicrobiana na redução dos microrganismos totais e S. mutans, enquanto a ação do óleo Melaleuca Alternifolia 0.5% foi semelhante à água destilada. O listerine e o óleo Melaleuca Alternifolia 2% apresentaram redução microbiana, respectivamente, de 11% e 9% para microrganismos totais, entretanto para S. mutans o listerine reduziu os níveis em 20% e o óleo Melaleuca Alternifolia 2% em 11%. Conclusão: O bochecho único com clorexidina 0,12% é eficaz na redução de níveis de microrganismos totais e S. mutans presentes na saliva. Ao comparar a clorexidina com o listerine e óleo Melaleuca Alternifolia 0,5% e 2% nas mesmas condições a eficácia da ação destas soluções é diminuída.
In vivo comparative evaluation of the efficacy of melaleuca oil, chlorhexidine and listerine against streptococcus mutans and total microorganisms in saliva
Keywords: Tea tree oil; Oils volatile; Streptococcus mutans; Saliva; Óleo de Melaleuca; Óleos essenciais; Streptococcus mutans; Saliva